Gratifikasi dalam Tindak Pidana Korupsi: Studi Normatif Pasca Berlakunya KUHP Nasional (Pusat Riset dan Inovasi Nasional, 2026)
This research is grounded in the enactment of Law Number 1 of 2023 concerning the National Criminal Code, which raises normative questions regarding the legal status of gratification within Indonesia’s anti-corruption framework. The study aims to analyze the normative position of gratification following criminal law codification and to assess its implications for evidentiary mechanisms under the Anti-Corruption Law. Employing a normative legal research method, this study applies statutory and conceptual approaches through comprehensive literature review of primary and secondary legal sources. The findings indicate that gratification remains regulated under the Anti-Corruption Law as lex specialis and is not nullified by the National Criminal Code. The reversal of the burden of proof mechanism continues to apply, although its interpretation must align with fundamental criminal law principles such as culpability and proportionality. The study concludes that systematic harmonization between both legal regimes is essential to ensure legal certainty and strengthen anti-corruption enforcement.